MicroRNA-21 and microRNA-148a affects PTEN, NO and ROS in canine leishmaniasis - De Freitas, Jéssica Henrique; Bragato, Jaqueline Poleto; Rebech, Gabriela Torres; Costa, Sidnei Ferro; Dos Santos, Marilene Oliveira; Soares, Matheus Fujimura; Eugênio, Flávia de Rezende; Dos Santos, Paulo Sérgio Patto; De Lima, Valéria Marçal Felix (Frontiers in Genetics, 2023)
Canine Visceral leishmaniasis (CanL) poses a severe public health threat in several countries. Disease progression depends on the degree of immune response suppression. MicroRNAs (miRs) modulate mRNA translation into proteins and regulate various cellular functions and pathways associated with immune responses. . MiR-21 and miR-148a can alter the parasite load and M1 macrophages are the principal cells in dogs' leishmanicidal activity. A previous study found increased miR-21 and miR-148a in splenic leukocytes (SL) of dogs with CanL using microarray analysis and in silico analysis, identified PTEN pathway targets. PTEN is involved in the immune regulation of macrophages. We measured PTEN and the production of reactive oxygen species (ROS) and nitric oxide (NO) after transfection SL of dogs with CanL with mimic and inhibition of miR-21 and miR-148a. PTEN levels increased, NO and ROS decreased in SLs from dogs with CanL. Inhibition of miRNA-21 resulted in PTEN increases; in contrast, PTEN decreased after miR-148a inhibition. Nitrite levels increased after transfection with miR-21 inhibitor but were decreased with miR-148a inhibitor. The increase in miR-21 promoted a reduction in ROS and NO levels, but miR-148a inhibition increased NO and reduced ROS. These findings suggest that miR-21 and miR-148a can participate in immune response in CanL affecting PTEN, NO, and ROS levels.